Therapeutic efficacy of a hybrid mandibular advancement device in the management of obstructive sleep apnea assessed with acoustic reflection technique - S S Agarwal; B Jayan; Sunil Kumar (Wolters Kluwer Medknow Publications, 2015)
Obstructive sleep apnea (OSA) is one of the most common forms of sleep-disordered breathing. Various treatment modalities include behavior modification therapy, nasal continuous positive airway pressure (CPAP), oral appliance therapy, and various surgical modalities. Oral appliances are noninvasive and recommended treatment modality for snoring, mild to moderate OSA cases and severe OSA cases when patient is not compliant to CPAP therapy and unwilling for surgery. Acoustic reflection technique (ART) is a relatively new modality for three-dimensional assessment of airway caliber in various clinical situations. The accuracy and reproducibility of acoustic rhinometry and acoustic pharyngometry assessment are comparable to computerized tomography and magnetic resonance imaging. This case report highlights the therapeutic efficacy of an innovative customized acrylic hybrid mandibular advancement device in the management of polysomnography diagnosed OSA cases, and the treatment results were assessed by ART.